2013
DOI: 10.1002/ep.11898
|View full text |Cite
|
Sign up to set email alerts
|

Solar powered charge stations for electric vehicles

Abstract: Every hour, the sun emits more energy onto the Earth's surface than our entire world population uses in one year (Green Fuel, 2013, http://www.greenfuelsolar.com/solar-fact-or-fiction/) Solar power provides us with the possibility of a cleaner and more renewable future. Global climate change as a result of greenhouse gases and the effects of low air quality caused by pollutants have become very substantial issues in our world today. The costs associated with greenhouse gas and air pollutant emissions, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 7 publications
(11 reference statements)
1
40
0
Order By: Relevance
“…The second category of research mainly targets the concerns of overload in grids as a result of EV charging [17]. Goldin et al [18] argued that solar-powered charging stations may significantly weaken the influence of EV charging on the local grid. Furthermore, lots are suitable locations for the incorporation of solar power into electrical grids because of the beneficial social values of shade and the convenience for vehicle charging.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The second category of research mainly targets the concerns of overload in grids as a result of EV charging [17]. Goldin et al [18] argued that solar-powered charging stations may significantly weaken the influence of EV charging on the local grid. Furthermore, lots are suitable locations for the incorporation of solar power into electrical grids because of the beneficial social values of shade and the convenience for vehicle charging.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, electric vehicles have one-tenth the number of parts that gasoline-powered vehicles have [3], thus requiring less maintenance, and saving drivers time and money. For instance, one study (cited in [3]) found that electric vehicle owners save about 46% in annual maintenance costs. Another economic value of electric vehicles is that energy operational costs are about one-third the fuel cost associated with internal combustion engine vehicles [5].…”
Section: Values Of Electric Vehiclesmentioning
confidence: 99%
“…Electric vehicles also help the nation reduce its reliance on foreign fossil fuels [1]. In addition, electric vehicles have one-tenth the number of parts that gasoline-powered vehicles have [3], thus requiring less maintenance, and saving drivers time and money. For instance, one study (cited in [3]) found that electric vehicle owners save about 46% in annual maintenance costs.…”
Section: Values Of Electric Vehiclesmentioning
confidence: 99%
See 2 more Smart Citations